Amidoximation hydrotalcite-antimonene composite material as well as preparation method and application thereof

By modifying the amidoxime group on the surface of the hydrotalc and loading it on the antimonylene matrix, amidoxime hydrotalc-antene composite material is formed for uranyl ion detection, the detection sensitivity and The problem of insufficient selectivity has achieved efficient and low-cost rapid on-site inspection.

CN119457046AActive Publication Date: 2025-02-18NANHUA UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411661452.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-18
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The prior art has problems of insufficient sensitivity and selectivity in uranyl ion detection, and the traditional detection methods and equipment are expensive and cumbersome, so they are not suitable for rapid on-site detection.

Method used

Using amidoxime-hydrotalcite-antene composite material as the modification electrode, a composite material with high conductivity and high specific adsorption is formed by modifying the amidoxime group on the surface of the hydrotalcite and loading it on the antimonyle matrix. Used for electrochemical detection of uranyl ions.

Benefits of technology

It realizes high sensitivity, high selectivity and easy-to-operate uranyl ion detection, which is low-cost and suitable for rapid on-site inspection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119457046A_ABST
    Figure CN119457046A_ABST
Patent Text Reader

Abstract

The invention discloses an amidoximation hydrotalcite-antimonene composite material and a preparation method and application thereof.The preparation method comprises the steps that firstly, the surface of hydrotalcite is modified with an amino group, then the amino group is used for grafting and modifying a cyano group, the cyano group is converted into a hydroximic acid group through an amidoximation reaction, and amidoximation hydrotalcite is obtained; the amidoximation hydrotalcite is dispersed to form amidoximation hydrotalcite colloidal dispersion liquid, then the amidoximation hydrotalcite colloidal dispersion liquid and antimonene dispersion liquid are mixed and stacked to form a two-dimensional layered composite material, and then the two-dimensional layered composite material is obtained through centrifugation and drying. The composite material not only can effectively inhibit agglomeration of antimonene and hydrotalcite nanosheets, but also can increase active sites of the material combined with uranyl ions, and when the composite material is applied to electrochemical detection of uranyl ions, the composite material has high conductivity and high stability of antimonene and high specific adsorption of hydrotalcite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an amidoximated hydrotalcite-antimonene composite material and a preparation method and application thereof, and in particular to an amidoximated hydrotalcite-antimonene composite material used as a modified electrode and a preparation method thereof, belonging to the technical field of composite material preparation. Background Art

[0002] In today's society, nuclear energy, as an important form of energy, occupies a prominent position in the global energy supply. However, the operation of the nuclear industry is accompanied by the production of a large amount of uranium-containing wastewater. The uranium element in it poses a potential threat to the environment and human health due to its high chemical toxicity and long-lived radioactivity. The World Health Organization has set a strict standard for uranium concentration in drinking water, which should not exceed 30μg / L. This requires us to have effective and real-time trace uranium detection methods.

[0003] Traditionally, fluorescence, atomic absorption spectrometry, and inductively coupled plasma mass spectrometry have been used to detect uranium content in water, which have high sensitivity and good detection limits. However, the implementation of these methods relies on expensive equipment and cumbersome sample pretreatment steps, which makes them unsuitable for on-site rapid detection.

[0004] In this context, electrochemical methods have become a highly promising alternative due to their ease of operation, low cost, and good selectivity, especially for rapid on-site screening. Electrode modification is a key strategy to improve the performance of electrochemical sensors, and the application of new high-performance materials has become a research focus. For example, antimonene, an emerging nitrogen-based two-dimensional material, exhibits excellent electrocatalytic performance and high electron transfer efficiency due to its unique wrinkled honeycomb atomic structure and large specific surface area, and has shown broad application prospects in many fields, such as energy storage and biomedicine. Nevertheless, the surface of antimonene lacks adsorption sites that specifically recognize uranyl ions, which limits its application as a probe material in uranyl ion detection.

[0005] Layered double hydroxides (LDHs, also known as hydrotalcite, have a general chemical formula of [M 2+ 1-x M 3+ x (OH - )2] x+ (A n- ) x / n mH2O, where M 2+ is a divalent metal cation, M 3+ is a trivalent metal cation, A n-As a two-dimensional structural material, amidoxime has been widely used in the adsorption field due to its low cost, high chemical stability and easy modification. The amidoxime group has a high chelating affinity for uranium and is currently recognized as one of the groups with excellent selectivity for uranium. It is a feasible solution to modify hydrotalcite with amidoxime for uranyl ion detection. However, amidoxime-modified hydrotalcite materials still have layered stacking and aggregation phenomena that lead to a reduction in active sites, as well as relatively low conductivity that affects electron transport. These factors have, to a certain extent, restricted their in-depth development in the field of electrochemical sensors.

[0006] Therefore, seeking new strategies to combine these advantageous materials, address the limitations of existing methods, and develop uranyl ion sensors with high sensitivity, selectivity, and adaptability to rapid on-site detection is a technical problem that needs to be solved urgently. Summary of the invention

[0007] In view of the technical problems existing in the prior art, the first object of the present invention is to provide an amidoxime hydrotalcite-antimonene composite material, which improves the selective adsorption performance of the material by using an amidoxime group with high chelating affinity for uranium as a modifying group of hydrotalcite, and at the same time loads the hydrotalcite on an antimonene matrix with high conductivity, which can effectively inhibit the agglomeration of antimonene and hydrotalcite nanosheets and increase the active sites for the material to bind to uranyl ions, so that the composite material has both the high conductivity and high stability of antimonene and the high specific adsorption of amidoxime hydrotalcite.

[0008] The second object of the present invention is to provide a method for preparing an amidoximated hydrotalcite-antimonene composite material, which has the advantages of low cost, simple operation and easy scalability.

[0009] The third object of the present invention is to provide an application of an amidoximated hydrotalcite-antimonene composite material, which is used as a modified electrode for electrochemical detection of uranyl ions, and has the advantages of high sensitivity, high selectivity, simple and rapid operation, etc., and is low in cost and fast and simple, and is suitable for rapid detection on site.

[0010] In order to achieve the above technical purpose, the present invention provides a method for preparing an amidoxime hydrotalcite-antimonene composite material, which comprises the following steps: firstly modifying the surface of the hydrotalcite with amino groups, then using the amino groups to graft-modify the cyano groups, wherein the cyano groups are converted into hydroxamic acid groups through an amidoxime reaction to obtain amidoxime hydrotalcite; the amidoxime hydrotalcite is dispersed to form an amidoxime hydrotalcite colloidal dispersion, which is then mixed with an antimonene dispersion to form a two-dimensional layered composite material, which is then centrifuged and dried to obtain the composite material.

[0011] The key to the technical solution of the present invention is to firstly perform amidoxime modification on hydrotalcite by using an amidoxime group having a high chelating affinity for uranium as a modifying group of hydrotalcite to improve the selective adsorption performance of the material. The specific modification process is to firstly perform amination on the hydrotalcite, and then perform cyanation and amidoximation to obtain amidoximated hydrotalcite. The principle of the amidoxime modification is that the hydroxyl group on the surface of the hydrotalcite undergoes a dehydration condensation reaction with the hydrolyzed silane coupling agent to graft the amino group, and then glutaraldehyde is used as a cross-linking agent, and the aldehyde group at one end thereof undergoes a condensation reaction with the primary amine group on the surface of the hydrotalcite to be grafted on the surface of the hydrotalcite, and the aldehyde group at the other end undergoes a condensation reaction with the primary amine group of 2,3-diamino-2-butenedinitrile to introduce a cyano group, and finally the cyano group undergoes an amidoxime reaction with hydroxylamine hydrochloride to obtain the amidoximated hydrotalcite. Subsequently, the few-layer antimonene solution and the hydrotalcite colloidal solution are uniformly mixed and stirred, so that the antimonene and hydrotalcite nanosheets can be stacked on each other to form a two-dimensional layered composite material, which greatly increases the active sites of the composite material. At the same time, the hydrotalcite is loaded on the antimonene matrix with high conductivity through the self-assembly effect of the two, which can not only effectively inhibit the agglomeration of antimonene and hydrotalcite nanosheets, but also increase the active sites for the material to bind to uranyl ions, so that the composite material has both the high conductivity and high stability of antimonene and the high specific adsorption of hydrotalcite.

[0012] As a preferred solution, the modification of amino groups on the surface of the hydrotalcite is achieved by hydrolysis of an aminosilane coupling agent, and a commonly used aminosilane coupling agent is KH-550.

[0013] As a preferred solution, the modification of cyano groups by grafting amino groups is achieved by cross-linking 2,3-diamino-2-butenedinitrile with glutaraldehyde through an amine-aldehyde condensation reaction.

[0014] As a preferred solution, the amidoxime reaction is carried out in an ethanol aqueous solution by adding anhydrous sodium carbonate to adjust the pH of the system.

[0015] As a preferred scheme, the preparation method of the amidoximated hydrotalcite material in the present invention is: after grafting and modifying the amino group of hydrotalcite, an amino-modified hydrotalcite material is obtained; after the amino-modified hydrotalcite material is grafted and modified with glutaraldehyde to formaldehyde group, an aldehyde-modified hydrotalcite material is obtained; the aldehyde-modified hydrotalcite material is subjected to a condensation reaction with 2,3-diamino-2-butenedinitrile to obtain a cyanated hydrotalcite material; the cyanated hydrotalcite material is subjected to an amidoximation reaction with hydroxylamine hydrochloride.

[0016] As a preferred scheme, the solid-liquid ratio of the hydrotalcite to the aminosilane coupling agent is (0.25-2.5) g: (1-10) mL; the reaction conditions for the grafting modification of the amino group are: temperature of 40-100° C., and time of 6-24 h; the solid-liquid ratio of the amino-modified hydrotalcite material to glutaraldehyde is (0.5-5) g: (1-20) mL; the reaction conditions for the grafting modification of the aldehyde group are: temperature of 20-100° C., and time of 2-12 h, and the mass ratio of the aldehyde-modified hydrotalcite material to 2,3-diamino-2-butene dinitrile is (0.1-2): (0.5-4); the conditions for the condensation reaction are: temperature of 20-80° C., and time of 2-12 h. The mass ratio of the cyanation-modified hydrotalcite material to hydroxylamine hydrochloride is (0.1-1):(0.2-2); the conditions of the amidoxime reaction are: temperature of 60-100° C., and time of 6-24 hours.

[0017] As a preferred solution, the amidoximation degree of the amidoximated hydrotalcite (i.e., the ratio of the number of amidoxim groups to the number of atoms in the hydrotalcite matrix) is 0.1 to 20 at.%, more preferably 1 to 10 at.%. If the amidoximation degree of the hydrotalcite is too low, the selective adsorption capacity for uranyl ions is insufficient, and the ideal detection effect cannot be achieved; if the amidoximation degree is too high, the amidoxim groups may react with other substances in the environment to generate additional electrochemical signals, thereby interfering with the detection of the target substance.

[0018] As a preferred solution, the amidoximated hydrotalcite has a size of 0.3-3 μm and a shape of at least one of flake, rod and sphere. Within the range selected by the present invention, the amidoximated hydrotalcite has excellent adsorption performance, and more preferably has a size of 0.5-1 μm and a flake shape.

[0019] As a preferred solution, the general structural formula of the hydrotalcite matrix is ​​[M 2+ 1-x M 3+ x (OH - )2] x+ (A n- ) x / n mH2O; where M 2+ With M 3+ The element ratio is (2-5):1; M 2+ Including Mg 2+ 、Ni 2+ and Zn 2+ At least one of 3+ Including Al 3+ and Fe 3+ At least one of n- Including CO3 2-、NO 3- and C1 - At least one of the following. It is further preferred that the hydrotalcite matrix is ​​nickel-aluminum hydrotalcite (chemical formula Ni 0.75 Al 0.25 (OH)2(NO3) 0.25 ), M 2+ With M 3+ The element ratio is 3: 1. Compared with other types of hydrotalcite, nickel-aluminum hydrotalcite has low preparation cost, is easier to obtain, has higher surface adsorption capacity and reaction activity, is conducive to the preparation of composite materials, and enhances the ability of composite materials to enrich uranyl ions.

[0020] As a preferred solution, the mass ratio of the amidoximated hydrotalcite colloidal dispersion to the antimonene dispersion is (1-4):1.

[0021] As a preferred solution, the concentration of the amidoximated hydrotalcite colloidal dispersion is 1 to 10 g / L, and more preferably 1 to 2 g / L.

[0022] The concentration and mass ratio of the amidoximated hydrotalcite colloidal dispersion to the antimonene dispersion in the present invention will significantly affect the number of amidoximated hydrotalcite nanosheets. If the concentration and volume of the amidoximated hydrotalcite nanosheets are too high, excessive agglomeration and stacking will occur, thereby reducing the active sites of the composite material and affecting the detection effect.

[0023] As a preferred solution, the concentration of the antimonene dispersion is 0.5-5 g / L, wherein the purity of antimonene is ≥95 wt.%, the thickness is from a single atomic layer to a hundred atomic layers, and the lateral size is ≥10 nm. It is further preferred that the concentration of the antimonene dispersion is 0.5-1 g / L, the purity of antimonene is ≥99 wt.%, the thickness is from a single atomic layer to twenty atomic layers, and the lateral size is ≥100 nm. If the thickness of antimonene is too large, its specific surface area will be reduced, thereby reducing its efficiency in compounding with hydrotalcite; at the same time, the increase in thickness also hinders the charge transfer inside the composite material, which is not conducive to its sensitivity as an electrochemical sensing probe.

[0024] As a preferred solution, the colloidal dispersion of amidoximated hydrotalcite uses at least one of water, ethanol, methanol, N,N-dimethylformamide, dimethyl sulfoxide and N-methylpyrrolidone as the dispersion, and the purity of the reagent is experimentally pure or above. In the present invention, amidoximated hydrotalcite is added to the selected dispersion, and a stable dispersion is formed after stirring, thereby reducing the stacking of hydrotalcite nanosheets. It is further preferred that the dispersion is at least one of anhydrous ethanol, N,N-dimethylformamide and N-methylpyrrolidone, and the purity of the reagent is analytically pure.

[0025] As a preferred solution, the mixing time is 1 to 12 hours. The mixing time selected in the present invention can fully achieve the stacking of amidoximated hydrotalcite and antimonene, and the mixing time is further preferably 1 to 2 hours.

[0026] The present invention also provides an amidoximated hydrotalcite-antimonene composite material obtained by the above preparation method. The composite material has both the high conductivity and high stability of antimonene and the high specific adsorption of amidoximated hydrotalcite.

[0027] Finally, the present invention also provides an application of the amidoximated hydrotalcite-antimonene composite material, which is used as a modified electrode for electrochemical detection of uranyl ions. The present invention uses the amidoximated hydrotalcite-antimonene composite material as a probe material to modify the surface of the working electrode of the electrochemical sensor, and obtains a method for electrochemical detection of uranyl ions with high sensitivity, high selectivity, and simple and rapid operation by utilizing the high conductivity and high stability of antimonene and the high specific adsorption of amidoximated hydrotalcite, and synergistically utilizing the layered structure formed by amidoximated hydrotalcite and antimonene. The method is low in cost, fast and simple, and suitable for rapid detection on site.

[0028] As a preferred solution, the preparation process of the modified electrode is as follows: the amidoximated hydrotalcite-antimonene composite material is mixed with a binder to obtain a uniform and stable suspension. An appropriate working electrode is selected and polished, and then the suspension is coated on the surface of the polished working electrode to form a layer of suspension film with uniform thickness. After the coated working electrode is placed in an oven for drying, the amidoximated hydrotalcite-antimonene composite material is fixed on the electrode surface by the action of the binder to obtain a working electrode modified by the amidoximated hydrotalcite-antimonene composite material.

[0029] As a preferred solution, the binder includes but is not limited to 1-20wt.% of Nafion, polyvinylidene fluoride, polyacrylic acid, polyvinyl alcohol, polytetrafluoroethylene, carboxymethyl cellulose, chitosan, sodium alginate, β-cyclodextrin and other oily or water-based binders suitable for amidoximated hydrotalcite-antimonene. It is further preferred that the liquid binder is 3-10wt.% of Nafion, polyvinylidene fluoride, polyacrylic acid, polyvinyl alcohol.

[0030] As a preferred solution, the conditions for the electrochemical detection are: pH 2-4, and enrichment time 2-10 minutes. At a relatively low pH, a large number of positively charged hydrogen ions will compete with uranyl ions for adsorption, occupying active sites on the surface of the composite material, hindering the complexation of the composite material with uranyl ions, and reducing the detection performance of the composite material; with the increase of pH value, the hydrogen ion content in the solution is relatively reduced, and U (VI) ions also exist almost in the form of uranyl ions, so the adsorption performance increases; and when the pH is too high, the type distribution of U (VI) ions gradually changes to a form dominated by other complexes, the uranyl ion content is greatly reduced, and the adsorption of U (VI) ions by the composite material is reduced.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1) The present invention provides an amidoxime hydrotalcite-antimonene composite material, which improves the selective adsorption performance of the material by using an amidoxime group with high chelating affinity for uranium as a modifying group of hydrotalcite, and loads the hydrotalcite on an antimonene matrix with high conductivity, which can effectively inhibit the agglomeration of antimonene and hydrotalcite nanosheets and increase the active sites for the material to bind to uranyl ions, so that the composite material has both high conductivity and high stability of antimonene and high specific adsorption of hydrotalcite.

[0033] 2) The amidoximated hydrotalcite-antimonene composite material of the present invention can be used as a probe material to modify the working electrode surface of an electrochemical sensor. By synergistically utilizing the high conductivity and high stability of antimonene and the high specific adsorption of amidoximated hydrotalcite, a method for electrochemically detecting uranyl ions with high sensitivity, high selectivity, simplicity and rapidity in operation is obtained. The method is low in cost, rapid and simple, and suitable for rapid on-site detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a flow chart for the preparation of amidoximated hydrotalcite-antimonene composite materials and the production of modified electrodes.

[0035] Figure 2 This is a schematic diagram of the atomic structure model of amidoxime-treated hydrotalcite-antimonene composite material.

[0036] Figure 3 It is the X-ray diffraction (XRD) spectrum of the amidoxime nickel aluminum hydrotalcite (AO-NiAl-LDHs), antimonene (antimonene) and the amidoxime nickel aluminum hydrotalcite-antimonene composite material (AO-NiAl-LDHs / antimonene) with mass ratios of 2:1, 3:1 and 4:1 respectively in Example 1.

[0037] Figure 4is the SEM picture of the amidoxime nickel aluminum hydrotalcite-antimonene composite material in Example 1 and Comparative Example 1, wherein Figure 4 (a) The mass ratio of AO-NiAl-LDHs to antimonene is 2:1; Figure 4 (b) The mass ratio is 5:1.

[0038] Figure 5 The modified electrodes in Example 1 (mass ratio of 2:1), Comparative Example 2 and Comparative Example 3 were prepared in the presence of 5 mM [Fe(CN)6] 3- / 4- CV graph of 0.1M KCl solution.

[0039] Figure 6 The modified electrodes in Example 1 (mass ratio of 2:1), Comparative Example 2 and Comparative Example 3 were prepared in the presence of 5 mM [Fe(CN)6] 3- / 4- EIS graph of 0.1M KCl solution.

[0040] Figure 7 It is a differential pulse voltammetry (DPV) diagram of uranyl ion detection in solutions of different pH values ​​in Example 1 (mass ratio is 2:1) and Comparative Example 4.

[0041] Figure 8 It is a differential pulse voltammetry (DPV) diagram of uranyl ion detection at different enrichment times in Example 1 (mass ratio is 2:1). DETAILED DESCRIPTION

[0042] In order to further illustrate the present invention, the contents of the present invention are described in detail below in conjunction with the examples. However, it should be understood that these examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention. The protection scope of the present invention is not limited to the following examples.

[0043] The preparation process of the composite material of the present invention and the preparation process of the modified electrode thereof are shown in the following figure: Figure 1 The schematic diagram of the atomic structure model of the composite material is shown in Figure 2 shown.

[0044] The preparation process of the amidoxime nickel aluminum hydrotalcite used in the examples and comparative examples of the present invention is as follows:

[0045] 0.015molNi(NO3)2, 0.005molA1(NO3)3, 0.04molNaOH and 0.01molNaNO3 were added to 100mL deionized water, stirred at room temperature for 1h, and then transferred to a 100mL reactor with a polytetrafluoroethylene liner, and reacted at 100℃ for 24h. After the reaction, the reactor was cooled to room temperature, the precipitate was collected by centrifugation, washed with deionized water until neutral, and then dried at 60℃ for 12h to obtain nickel aluminum hydrotalcite (NiA1-LDHs) powder.

[0046] Weigh 0.5g NiAl-LDHs and 5mL KH-550 silane coupling agent respectively and add them to 50mL anhydrous ethanol, stir at 80°C for 12h, wash the solid product obtained by the reaction with anhydrous ethanol and deionized water three times respectively, take the centrifugal precipitate and dry it at 60°C for 12h to obtain amino-modified nickel aluminum hydrotalcite (NH2-NiAl-LDHs). Take 0.5g NH2-NiAl-LDHs and 1mL glutaraldehyde (12%) and add them to 100mL anhydrous ethanol, stir at room temperature for 3h, wash the solid product after the reaction with anhydrous ethanol by centrifugation three times, take the precipitate and dry it at 60°C for 12h to obtain aldehyde-modified nickel aluminum hydrotalcite (CHO-NiAl-LDHs).

[0047] 0.5 g of CHO-NiAl-LDHs and 0.5 g of 2,3-diamino-2-butenedinitrile were weighed and dispersed in 100 mL of anhydrous ethanol and stirred at room temperature for 3 h. The solid product after the reaction was washed three times by centrifugation with anhydrous ethanol and dried at 60 °C for 12 h to obtain cyanide-modified nickel aluminum hydrotalcite (CN-NiAl-LDHs).

[0048] Weigh 0.5 g of NH2OH·HCl and dissolve it in 100 mL of ethanol solution (V 乙醇 :V 水 =9:1), anhydrous sodium carbonate was added to adjust the pH value of the solution to 7.0, and then 0.25g of CN-NiAl-LDHs was added, and the reaction was stirred at 80°C for 6h to allow the cyano group to completely undergo amidoximation reaction. The suspension after the reaction was centrifuged and washed several times with anhydrous ethanol and deionized water until the supernatant was neutral, and the precipitate was dried at 60°C for 12h to obtain AO-NiAl-LDHs powder.

[0049] Example 1

[0050] 1) Preparation of nickel aluminum amidoxime hydrotalcite-antimonene

[0051] According to the mass ratio of AO-NiAl-LDHs to antimonene of 2:1, 3:1 and 4:1, 50 mg, 75 mg and 100 mg of amidoxime nickel aluminum hydrotalcite (chemical formula Ni 0.75Al 0.25 (OH)2(NO3) 0.25 , amine oximation degree of 5.0at.%, size of 0.5μm, flake) were added to 50mL of anhydrous ethanol respectively, and a stable dispersion was formed after stirring for 1h. At the same time, 25mg of antimonene powder was re-dispersed in 25mL of anhydrous ethanol by ultrasound for 30min to obtain an antimonene dispersion (wherein the purity of antimonene was 99%, the thickness was from a single atomic layer to 30 atomic layers, and the lateral size was 300nm to 1μm). Then the two were evenly mixed, stirred for 12h, so that antimonene and hydrotalcite nanosheets were stacked with each other through van der Waals force, and finally centrifuged at a centrifugal speed of 10000rpm / min and a centrifugal time of 20min. The centrifugal precipitate was dried at 60°C for 12h to obtain an amidoximated nickel aluminum hydrotalcite-antimonene composite material powder.

[0052] XRD characterization of the amidoxime nickel aluminum hydrotalcite-antimonene composite material was carried out. Figure 3 The X-ray diffraction patterns of AO-NiAl-LDHs, antimonene and AO-NiAl-LDHs / antimonene are shown. The XRD spectrum of AO-NiAl-LDHs has classic characteristic peaks of (003), (006), (009), (110) and (113) crystal planes of hydrotalcite materials at 2θ of 11.60°, 23.13°, 35.06°, 61.09° and 62.33°; the XRD spectrum of antimonene shows characteristic diffraction peaks at 2θ of 23.71°, 28.73°, 40.11°, 41.97° and 51.63°, corresponding to the (003), (012), (104), (110) and (202) crystal planes of antimonene nanosheets, respectively, which match the PDF standard card (PDF#35-0732) of bulk Sb. Among them, the XRD spectra of AO-NiAl-LDHs / antimonene composites with different mass ratios all have typical characteristic peaks of hydrotalcite and antimonene, indicating that antimonene and hydrotalcite nanosheets are stacked with each other through van der Waals forces to form a layered structure, and the composite material is successfully prepared.

[0053] Figure 4 (a) is a SEM image of a composite material of nickel aluminum hydrotalcite-antimony with a mass ratio of 2:1. It can be seen that the hydrotalcite material is evenly distributed on the surface of antimony. For the composite materials obtained with a mass ratio of 3:1 and 4:1, the number of hydrotalcite nanosheets increased slightly, but was accompanied by partial agglomeration. Therefore, there was no significant difference in the detection performance of the composite materials with the three ratios.

[0054] 2) Electrode preparation

[0055] The electrode surface was polished with 0.05, 0.3 and 1.0 μm aluminum oxide powders, respectively, and then placed in nitric acid (50%), anhydrous ethanol and deionized water for 60 seconds in sequence, and finally dried with nitrogen.

[0056] Weigh 5 mg of the amidoximated hydrotalcite-antimonene composite powder prepared in Example 1 (the mass ratio of amidoximated hydrotalcite to antimonene is 2:1) in 5 mL of anhydrous ethanol solution, add 50 μL of Nafion solution and mix well to obtain a 1 mg / mL amidoximated hydrotalcite-antimonene solution. Take 10 μL of the 1 mg / mL amidoximated hydrotalcite-antimonene solution and evenly drop it on the surface of the glassy carbon electrode, dry it at 40°C for 12 hours, and obtain the modified working electrode (AO-NiAl-LDHs / antimonene / GCE).

[0057] Comparative Example 1

[0058] The difference between this comparative example and Example 1 is that the mass ratio of amidoxime nickel aluminum hydrotalcite to antimonene is 5:1, and the other steps and conditions are the same to obtain an AO-NiAl-LDHs / antimonene composite material, whose SEM image is as follows: Figure 4 (b) Compared with Figure 4 (a) At this time, the addition of excessive AO-NiAl-LDHs nanosheets causes more agglomeration and stacking of AO-NiAl-LDHs on the surface of antimonene, which will affect the generation of active sites of the composite material and the electrochemical detection performance of the modified electrode to a certain extent.

[0059] Comparative Example 2

[0060] The only difference between this comparative example and Example 1 is that no antimonene solution is added, and the remaining steps and conditions are the same, thereby obtaining an AO-NiAl-LDHs modified glassy carbon electrode (AO-NiAl-LDHs / GCE).

[0061] Comparative Example 3

[0062] The only difference between this comparative example and Example 1 is that AO-NiAl-LDHs is not added, and the remaining steps and conditions are the same, thereby obtaining an antimonene-modified glassy carbon electrode (antimonene / GCE).

[0063] Comparative Example 4

[0064] The difference between this comparative example and Example 1 is that AO-NiAl-LDHs is replaced by NiAl-LDHs, and the other steps and conditions are the same, thereby obtaining a NiAl-LDHs / antimonene modified glassy carbon electrode (NiAl-LDHs / antimonene / GCE).

[0065] Application Test Example 1

[0066] The materials of Example 1 (mass ratio is 2:1), Comparative Example 2, Comparative Example 3 and Comparative Example 4 are respectively used as working electrodes, Ag / AgCl is used as reference electrode, and platinum wire is used as auxiliary electrode. The three together constitute a three-electrode system, and electrochemical tests are performed on them using Shanghai Chenhua CHI660D electrochemical workstation.

[0067] In the presence of 5.0 mM [Fe(CN)6] 3- / 4- The electrochemical characterization was carried out by cyclic voltammetry (CV) in 0.1M KCl solution and 0.1M KCl solution. The CV parameters were as follows: scan rate 0.1V / s, high potential 0.8V, low potential -0.3V, sampling interval 0.001V, duration 2s, sensitivity 1×10 -4 A / V. The results are as follows Figure 5 As shown in the figure, a pair of symmetrical redox peaks appeared in the cyclic voltammograms of all modified electrodes. When AO-NiAl-LDHs and antimonene were modified on the glassy carbon electrode, the peak current corresponding to AO-NiAl-LDHs was significantly smaller than that of antimonene. The reason is that compared with antimonene, the conductivity and charge transfer ability of the hydrotalcite material itself are poor, which hinders the [Fe(CN)6] 3- / 4- When AO-NiAl-LDHs / antimonene is modified on the glassy carbon electrode, the peak current is significantly increased compared with the previous two, indicating that antimonene and hydrotalcite nanosheets combine to form a stacked layered structure, reducing the agglomeration of the two materials and facilitating the charge transfer on the surface of the material and [Fe(CN)6] 3- / 4- These results confirm the successful preparation of the composite material and its modification on the electrode surface, and also confirm the synergistic effect between amidoxime nickel aluminum hydrotalcite and antimonene.

[0068] In the presence of 5.0 mM [Fe(CN)6] 3- / 4- Electrochemical impedance spectroscopy (EIS) was performed in 0.1M KCl solution with the following EIS parameters: frequency range 0.1 Hz to 1000000 Hz, amplitude 0.005 V, and duration 2 s. Figure 6 As shown in the figure, the electrochemical impedance spectroscopy of the modified electrode shows a typical semicircle, and the charge transfer resistance (R ct) is equal to the semicircle diameter of the Nyquist plot, and its size is related to the electrochemical properties of the electrode surface modification material. The R values ​​of AO-NiAl-LDHs, antimonene, and AO-NiAl-LDHs / antimonene were obtained by fitting with ZView software. ct The values ​​are 3862Ω, 1081Ω, and 738.8Ω, respectively. From the results, it can be seen that antimonene has better conductivity than hydrotalcite. After the glassy carbon electrode was modified with amidoximated hydrotalcite-antimonene composite material, R ct The value is further reduced, showing the best charge transfer ability and conductivity. This method is consistent with the results of the CV method, further confirming the successful preparation of the probe material.

[0069] Application Test Example 2

[0070] 1) Electrochemical detection performance of working electrodes at different pH values

[0071] The modified electrodes of Example 1 (mass ratio of 2:1) and Comparative Example 4 were selected, and then the solutions with uranyl ion concentration of 0.1 mg / L and pH values ​​of 2.0, 2.3, 2.5, 3.0, 3.5, 4.0, 4.5 and 5.0 were detected by differential pulse voltammetry (DPV). All electrochemical test experiments were completed in 0.1M KCl solution, and the parameters of differential pulse voltammetry (DPV) were as follows: potential increment of 4mV, amplitude of 50mV, pulse width of 50ms, sampling width of 16.7ms, pulse period of 0.2s, duration of 2s, and scanning range of -0.8 to 1.0V.

[0072] The results are as follows Figure 7As shown. With the increase of pH value, the reduction peak current first increases, and then gradually decreases after reaching the peak value. The reason for this phenomenon may be that at a lower pH, a large number of positively charged hydrogen ions will compete with uranyl ions for adsorption, occupy the active sites on the surface of the material, hinder the complexation of the material with uranyl ions, and reduce the detection performance of the material. When the pH rises to 2.5, the hydrogen ion content in the solution is relatively reduced, and the U(VI) ions also exist almost in the form of uranyl ions, so the peak current at this time reaches the maximum value. However, when the pH value is higher than 3, the type distribution of U(VI) ions gradually changes to a form dominated by other complexes, and the uranyl ion content is greatly reduced, which is also not conducive to the adsorption of U(VI) ions by the material, so the peak current also decreases. Therefore, it is further preferred that the pH is 2.3-3.0, and the optimal pH value is further determined to be 2.5. At the same time, the experimental results of electrochemical detection of uranyl ions by AO-NiAl-LDHs / antimonene / GCE of Example 1 and NiAl-LDHs / antimonene / GCE of Comparative Example 4 were compared, indicating that the amidoxime group produced a strong adsorption effect during the detection process, thereby increasing the detection performance of the composite material.

[0073] 2) Electrochemical detection performance of working electrodes at different enrichment times

[0074] The modified electrode of Example 1 (mass ratio of 2:1) was selected, and then the peak currents of enrichment time of 0, 1, 2, 3, 4, 5, 6, 8, 10, 12 and 16 min were studied respectively; the solution with uranyl ion concentration of 0.1 mg / L was detected by differential pulse voltammetry (DPV). All electrochemical test experiments were completed in 0.1M KCl solution, and the parameters of differential pulse voltammetry (DPV) were as follows: potential increment of 4mV, amplitude of 50mV, pulse width of 50ms, sampling width of 16.7ms, pulse period of 0.2s, duration of 2s, and scanning range of -0.8 to 1.0V.

[0075] Figure 8 The peak current and the enrichment time are shown in Figure 2. The peak current gradually increases with the enrichment time until the active sites on the surface of the material almost reach adsorption saturation after 10 minutes, and the current does not increase significantly.

Claims

1. A method for preparing an amidoximated hydrotalcite-antimonene composite material, characterized in that: Firstly, amino groups are modified on the surface of hydrotalcite, and then cyano groups are grafted and modified by amino groups. The cyano groups are converted into hydroxamic acid groups through amidoxime reaction to obtain amidoxime hydrotalcite; the amidoxime hydrotalcite is dispersed to form an amidoxime hydrotalcite colloidal dispersion, which is then mixed with an antimonene dispersion to form a two-dimensional layered composite material, which is then centrifuged and dried to obtain the composite material.

2. The method for preparing an amidoximated hydrotalcite-antimonene composite material according to claim 1, characterized in that: The modification of amino groups on the surface of hydrotalcite is achieved by hydrolysis of aminosilane coupling agent; The grafting modification of cyano groups with amino groups is achieved by cross-linking 2,3-diamino-2-butenedinitrile with glutaraldehyde through an amine-aldehyde condensation reaction.

3. The method for preparing the amidoximated hydrotalcite-antimonene composite material according to claim 2, characterized in that: The amidoximation degree of the amidoximated hydrotalcite is 0.1 to 20 at.%.

4. The method for preparing the amidoximated hydrotalcite-antimonene composite material according to claim 1, characterized in that: The general structural formula of the hydrotalcite matrix is ​​[M 2+ 1-x M 3+ x (OH - )2] x+ (A n- ) x / n mH2O; Among them, M 2+ With M 3+ The element ratio is (2-5):1; M 2+ Including Mg 2+ 、Ni 2+ and Zn 2+ At least one of; M 3+ Including Al 3+ and Fe 3+ At least one of; A n- Including CO3 2- 、NO 3- and C1 - At least one of .

5. The method for preparing the amidoximated hydrotalcite-antimonene composite material according to any one of claims 1 to 4, characterized in that: The mass ratio of the amidoximated hydrotalcite colloidal dispersion to the antimonene dispersion is (1-4):1; The concentration of the amidoximated hydrotalcite colloidal dispersion is 1 to 10 g / L; The concentration of the antimonene dispersion is 0.5-5 g / L, wherein the purity of the antimonene is ≥95 wt.%, the thickness is from a single atomic layer to a hundred atomic layers, and the lateral size is ≥100 nm.

6. The method for preparing the amidoximated hydrotalcite-antimonene composite material according to claim 5, characterized in that: The amidoximated hydrotalcite colloidal dispersion liquid uses at least one of water, ethanol, methanol, N,N-dimethylformamide, dimethyl sulfoxide and N-methylpyrrolidone as the dispersion liquid.

7. The method for preparing the amidoximated hydrotalcite-antimonene composite material according to claim 1, characterized in that: The mixing time is 1 to 12 hours.

8. An amidoximated hydrotalcite-antimonene composite material, characterized in that: Obtained by the preparation method according to any one of claims 1 to 7.

9. The use of the amidoximated hydrotalcite-antimonene composite material according to claim 8, characterized in that: It is used as a modified electrode for the electrochemical detection of uranyl ions.

10. The use of the amidoximated hydrotalcite-antimonene composite material according to claim 9, characterized in that: The conditions for the electrochemical detection are: pH 2-4, and enrichment time 2-10 min.

Citation Information

Patent Citations

  • Preparation method of nano LDH (layered double hydroxides)

    CN105502445A

  • Two-dimensional material nanometer roll as well as preparation method and application thereof

    CN108217608A

  • PVC formulations with low water vapor permeability

    US20240052152A1

  • Cosmetic agents having increased fragrance intensity and persistence

    WO2007068339A1